Effect of Fish-Based Diet on Malnourished Children: A Systematic Review - La Banudi La Banudi; Purnomo Leksono; M. Anas Anasiru (Iranian Journal of Medical Sciences, 2024)
Background: Malnutrition in children is mainly caused by the lack of protein and fat intake which harms their ability to grow and survive. Accurate data on the benefits of fish-based foods on the nutritional status of children is limited. The present systematic review aimed to provide an overview of published articles on the nutritional value of fish-based foods for children.Methods: A systematic review was performed during 2000-2021 by searching Science Direct, Cochrane Library, PubMed, ProQuest, and Wiley Online Library databases. The full text of selected articles in English was screened based on the inclusion and exclusion criteria. Included articles were all experimental studies (randomized control trial, quasi-randomized trial) or mixed methods studies involving malnourished children. The study was reported under the preferred reporting items for systematic reviews and meta-analyses guidelines. The risk of bias was assessed using the Cochrane tool.Results: A total of 330,859 articles were screened, out of which eight articles were included in the systematic review. Interventions included fish-based foods and beverages such as wafer bars, Jemawut-tuna cookies, Amizate in chocolate drink, dried fish powder, flaxseed oil supplemented with fish oil capsules, and porridge fortified with fish powder. Primary or secondary outcomes were the determination of zinc level, height growth, erythrocyte n-3 polyunsaturated fatty acid content, safety and acceptability, intestinal integrity, and cognitive development. The results showed that dried fish powder produced the most significant effect on body weight.Conclusion: The consumption of dried fish powder had positive effects on the recovery of malnourished children.